2016
DOI: 10.1002/2015jb012502
|View full text |Cite
|
Sign up to set email alerts
|

Remagnetization of lower Silurian black shale and insights into shale gas in the Sichuan Basin, south China

Abstract: The organic‐rich lower Silurian shale of the Longmaxi Formation in the Sichuan Basin is the most important target for shale‐gas exploration in China. Most Paleozoic rocks of the Sichuan Basin have experienced extraordinarily pervasive remagnetizations. To test a hypothesized connection between hydrocarbon generation and remagnetization and contribute to shale‐gas exploration in the region, we undertook an integrated magnetic, geochemical, and petrographic study of 160 specimens from the shale. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…(a) The map showing the temporal‐spatial variation of the Triassic remagnetization in South China. The dark green, red, and light green pentagram denotes the location where Early‐Middle Triassic (T 1‐2 , Jiao et al, ), Middle Triassic (T 2 , this study), and Late Triassic (T 3 ; Zhang et al, ) remagnetization was observed, respectively. The curved arrow shows the regional younging trend of the Triassic remagnetization in South China.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…(a) The map showing the temporal‐spatial variation of the Triassic remagnetization in South China. The dark green, red, and light green pentagram denotes the location where Early‐Middle Triassic (T 1‐2 , Jiao et al, ), Middle Triassic (T 2 , this study), and Late Triassic (T 3 ; Zhang et al, ) remagnetization was observed, respectively. The curved arrow shows the regional younging trend of the Triassic remagnetization in South China.…”
Section: Discussionmentioning
confidence: 73%
“…Unlike the widely recorded Late Mesozoic remagnetization in South China (e.g., Dobson & Heller, ; Evans et al, ; Gao et al, ; Huang et al, ; Huang & Opdyke, ; Jing et al, ; Jing et al, ; Kent et al, ; Zhang et al, ), a Triassic overprint was previously reported by only a few studies (Jiao et al, ; Zhang et al, ). Zhang et al () reported a Late Triassic (T 3 ) remagnetization from Sichuan, western South China, and Jiao et al () recently reported an Early‐Middle Triassic (T 1–2 ) remagnetization component from Zhejiang, eastern South China. These records, together with the Middle Triassic (T 2 ) remagnetization recognized in middle South China (this study), present a temporal‐spatial pattern of the Triassic remagnetization that appears to exhibit a younging trend of remagnetization from the east to the west of South China (Figure ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To constrain the chemical processes associated with hydrocarbon migration into the carbonate reservoir rocks, an integrated paleomagnetic, rock magnetic, and petrographic study was conducted along a transect across the outcrop. This investigation also aimed to provide important insights into the relationship between pervasive remagnetization and hydrocarbon occurrences in south China (Wang & Van Der Voo, ; Zhai, ; Zhang et al, ). The results have the potential to improve yield from Ediacaran dolomite formation, which is the largest single carbonate gas reservoir in China.…”
Section: Introductionmentioning
confidence: 99%